THE EXISTENCE AND PROTECTION OF ULAYAT RIGHTS IN INDIGENOUS COMMUNITIES WITHIN THE FRAMEWORK OF POSITIVE LAW IN INDONESIA - Rubiati, Betty (Fakultas Hukum Universitas Padjadjaran, 2024)
Ulayat Rights are the highest rights of indigenous law communities to land. Normatively, protection of the rights of indigenous law communities is contained in several related laws and regulations, but in practice, Ulayat Rights of indigenous law communities often become the object of dispute/conflict, both with the government and with private parties who need land, so that they are often eliminated and detrimental to the rights of indigenous law communities. The aim of this research is to obtain an overview of the criteria for determining the existence of Ulayat rights of indigenous law communities and the legal protection of them when dealing with outside parties from a positive legal perspective in Indonesia. The approach method used is a normative juridical approach, namely tracing, studying and researching secondary data related to this research material. A juridical approach is used considering the problems studied revolve around the relationship between a regulation and other regulations, namely regulations regarding land, forestry and plantation law. The research results show that recognition of the existence of Ulayat rights of indigenous law communities is limited as long as they still exist and must fulfill several elements as specified in several statutory regulations. Protection of traditional rights is contained in the constitution, sectoral legislation and regional regulations, but in reality there are still frequent disputes/conflicts, this shows that the protection of Ulayat rights of indigenous law communities is still not optimal.